The Figure of the Migrant: Tommy Wieringa’s Intellectual Intervention - Heynders, Odile (Werkwinkel, 2017)
In today’s transforming European public sphere various literary authors position themselves publicly and engagingly in the debate on migration and exclusion. Dutch writer Tommy Wieringa is a clear voice in this context: his ideas on the topic are meaningfully expressed in literary novels. This article analyses Wieringa’s position as an authoritative public intellectual speaking with great moral weight about the figure of the migrant. Drawing on positioning theory, the main claim of the article will be that Wieringa’s literary articulation of migration contributes to the societal discussion and underlines a specific type of moral knowledge as well as an appeal to human solidarity.